Sattjeni: Daughter, Wife and Mother of the Governors of Elephantine during the End of the Twelfth Dynasty - Sánchez-León, Juan Carlos (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
For the last six years a multidisciplinary team of the Universidad de Jaén has been working in some of the funerary complexes of the second half of the Twelfth Dynasty in Qubbet el-Hawa. The present paper analyzes new material found in the funerary complex called QH33 and dated to that period. One of the new pieces of evidence is a ceramic with a hieratic inscription in which is mentioned a certain woman named Sattjeni and described with the title of “Daughter of ḥ Ꜣ tj- Ꜣ”. This personage also appears in other funerary contexts, which allows us to reconstruct the genealogy and history of the rulers of Elephantine during the Late Twelfth Dynasty.